Investigation of Vortex Rings for Free Jet and Synthetic Jet at Various Reynolds Numbers and Strouhal Numbers. (13th August 2020) - Chang, Jianlong; Zheng, Shizhen; Du, Yang; Xu, Junjie; Liu, Yanchen; Guo, Baoquan; Pan, Yutian; Han, Bing
Abstract : The behaviors of vortex rings for free jet and synthetic jet with various Reynolds numbers and Strouhal numbers are numerically studied by the k-ε model. The positions of the leading vortex of free jet are investigated under the three different conditions, and the effect of Strouhal number on the vortex ring is analyzed in detail. The results show that different Reynolds numbers lead to different positions for the shedding of the vortex rings. During the movement of the vortex rings, the symmetry of the vortex ring in synthetic jet retains in good state, and the vortex rings do not break up with well-arranged distributions. The distance between two adjacent vortex rings near the synthetic jet exit has the close link between the Strouhal number yet is independent of the Reynolds numbers.